High-impact human capital strategy : addressing the 12 major challenges today's organizations face - Phillips, Jack J., 1945-; Phillips, Patricia Pulliam (American Management Association, 2015)
Traditionally, human resources has focused on recruiting good people, preparing them for assignments, motivating them to perform, and retaining them. These functions remain essential, but to be successful in turbulent times like ours, human capital strategy needs to be broader and much more far-reaching. High-Impact Human Capital Strategy examines 12 critical forces that must be considered: globalization, changes in workforce demographics, skill shortages and mismatches in labor markets, environmental matters, and more. It shows how to in corporate each into an effective overall plan, and ho.